Women trafficking and the risk of contracting HIV/AIDS among the trafficked in Edo State (2009)
Women trafficking and HIV/AIDS have affected the country adversely and has posed a threat to the development of the nation. Although studies have documented the contribution of commercial sex workers of long truck drivers towards HIV/AIDS, there is dearth of knowledge about the phenomena of women trafficking and HIV/AIDS. This study therefore focused on the risk of contracting HIV/AIDS amongst trafficked girls in the two rehabilitation centres in Edo State. Qualitative techniques, which through, a case study, in –depth interviews and Focus Group Discussion were used in eliciting data. Content analysis was used in the presentation of findings. The study revealed that most trafficked victims have very little or no knowledge about HIV/AIDS and its prevention before they were trafficked. Data showed improved knowledge of HIV/AIDS during the process of rehabilitation after they had been trafficked. The study observed that most of the trafficked girls refused to test for their HIV-status because they were involved in high-risk sexual behavior (unprotected sex) before rehabilitation to avoid stigma associated with HIV/AIDS if they tested positive. The most known and prefers means of preventing HIV/AIDS amongst trafficked victim is condom use. However data showed that, in actual practice, the use of condom is low especially with regular and close partners. It was also revealed that only one object is shared amongst subjects in the collection of blood, pubic and nails during the oath taking process and this is done to ensure that the girls are bound to their sponsor’s instructions in the course of being trafficked in order to avoid repercussions. Following these findings, the study recommends that effect to combat women trafficking and HIV/AIDS be intensified through poverty alleviation, sensitization against women trafficking and HIV?AIDS, reduction of stigmatization towards HIV/AIDS and empowerment of trafficked girls who have been rehabilitated to reduce recidivism